2010
DOI: 10.1016/j.tcb.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

NuMA after 30 years: the matrix revisited

Abstract: The large Nuclear Mitotic Apparatus (NuMA) protein is an abundant component of interphase nuclei and an essential player in mitotic spindle assembly and maintenance. With its partner, cytoplasmic dynein, NuMA uses its cross-linking properties to tether microtubules to spindle poles. NuMA and its invertebrate homologues play a similar tethering role at the cell cortex, thereby mediating essential asymmetric divisions during development. Despite its maintenance as a nuclear component for decades after the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 89 publications
7
156
0
1
Order By: Relevance
“…Similarly, NuMA was recruited to ablation-created minus-ends when dynein was inhibited by p150-CC1 over-expression (Figure 2-figure supplement 1A,B). Thus, NuMA localizes to minus-ends without dynein carrying it there -consistent with early observations in extract asters and spindles (Gaglio et al, 1996;Heald et al, 1997) but in contrast to the prevailing view that dynein delivers NuMA to minus-ends (Merdes et al, 2000;Radulescu and Cleveland, 2010). Slower NuMA accumulation kinetics after p50 overexpression suggest that dynein-dynactin-NuMA complex formation may aid rapid NuMA recruitment, but dynein 'Walk and Pile-up' alone cannot explain NuMA's minus-end affinity ( Figure 2D,E).…”
Section: Numa Localizes To Minus-ends Independently Of Dyneinsupporting
confidence: 87%
“…Similarly, NuMA was recruited to ablation-created minus-ends when dynein was inhibited by p150-CC1 over-expression (Figure 2-figure supplement 1A,B). Thus, NuMA localizes to minus-ends without dynein carrying it there -consistent with early observations in extract asters and spindles (Gaglio et al, 1996;Heald et al, 1997) but in contrast to the prevailing view that dynein delivers NuMA to minus-ends (Merdes et al, 2000;Radulescu and Cleveland, 2010). Slower NuMA accumulation kinetics after p50 overexpression suggest that dynein-dynactin-NuMA complex formation may aid rapid NuMA recruitment, but dynein 'Walk and Pile-up' alone cannot explain NuMA's minus-end affinity ( Figure 2D,E).…”
Section: Numa Localizes To Minus-ends Independently Of Dyneinsupporting
confidence: 87%
“…We first addressed whether NuMA (Nuclear Mitotic Apparatus protein) (14)(15)(16)(17)(18)(19), one of the conserved polar proteins, is localized to the cell cortex as well as spindle poles during cell division by using HeLa cells as a control (16). Immunostaining experiments showed that NuMA is localized to the nucleus during interphase, as reported previously (15), and to spindle poles throughout mitosis (Fig.…”
Section: Acd Preferentially Occurs In Human Neuroblastoma Cells With Asupporting
confidence: 64%
“…32 Furthermore, a recent study in C. elegans established a role for CDK-1 as an inhibitor of meiotic spindle rotation and proposed a model in which Cdk-1 inhibits cytoplasmic dynein activity by preventing its interaction with LIN-5, a NuMA ortholog. 33 While the preferred localization of a subset of NuMA to the meiotic spindle attached to the animal cortex is unknown, our results identify Cdc6 as the first molecular marker that displays such asymmetric pole localization at the time of spindle rotation and attachment to the oocyte's animal cortex.…”
Section: Discussionmentioning
confidence: 99%